290. Impact of follow up blood cultures on outcomes of patients with gram-negative bloodstream infections. (31st December 2020) - Amipara, Rajiv G; Winders, Hana R; Justo, Julie Ann; Bookstaver, P B; Kohn, Joseph; Al-hasan, Majdi
Abstract: Background: Importance of follow up blood cultures (FUBC) for Staphylococcus aureus bloodstream infections (BSI) is well known, but the role of FUBC in gram-negative BSI remains controversial. This retrospective cohort study examined the association between obtaining FUBC and mortality in patients with gram-negative BSI. Methods: Adults with first episodes of community-onset monomicrobial BSI due to gram-negative bacilli hospitalized at Prisma Health-Midlands hospitals in Columbia, South Carolina, USA from January 1, 2010 to June 30, 2015 were identified. Patients who died or were discharged from hospital within 72 hours of collection of index blood culture were excluded to minimize impact of survival and selection biases on results, respectively. FUBC were defined as repeat blood cultures obtained between 24 and 96 hours from initial positive blood culture. Cox proportional hazards regression model was used to examine association between obtaining FUBC and 28-day all-cause mortality. Results: Among 766 patients with gram-negative BSI, 219 (28.6%) had FUBC obtained and 15 of 219 (6.8%) FUBC were persistently positive. Overall, median age was 67 years, 438 (57%) were women, 457 (60%) had urinary source of infection, and 426 (56%) had BSI due to Escherichia coli . Mortality was significantly lower in patients who had FUBC obtained than in those who did not have FUBC (6.3% vs. 11.7%, log-rank p=0.03). Obtaining FUBC was independently associated with reduced mortality (hazards ratio [HR] 0.49, 95%CI: 0.25–0.90) after adjustments for age (HR 1.35 per decade, 95% CI: 1.13–1.61), cancer (HR 5.90, 95% CI: 3.53–9.84), Pitt bacteremia score (HR 1.38 per point, 95% CI: 1.26–1.50), and inappropriate empirical antimicrobial therapy (HR 2.37, 95% CI: 1.17–4.39). Conclusion: Obtaining FUBC was associated with improved survival in hospitalized patients with gram-negative BSI. These observations are consistent with the results of recent publications from Italy and North Carolina supporting utilization of FUBC in the management of gram-negative BSI. Disclosures: Julie Ann Justo, PharmD, MS, BCPS-AQ ID, bioMerieux (Speaker's Bureau)TRC Healthcare (Speaker's Bureau)